The recovery status from delayed graft function can predict long-term outcome after deceased donor kidney transplantation. Issue 1 (December 2017) - Lee, Juhan; Song, Seung; Lee, Jee; Kim, Deok; Lee, Jae; Kim, Beom; Kim, Myoung; Huh, Kyu
Abstract The effect of delayed graft function (DGF) recovery on long-term graft outcome is unclear. The aim of this study was to examine the association of DGF recovery status with long-term outcome. We analyzed 385 recipients who underwent single kidney transplantation from brain-dead donors between 2004 and 2015. Patients were grouped according to renal function at 1 month post-transplantation: control (without DGF); recovered DGF (glomerular filtration rate [GFR] ≥ 30 mL/min/1.73 m2 ); and incompletely recovered DGF group (GFR < 30 mL/min/1.73 m2 ). DGF occurred in 104 of 385 (27%) recipients. Of the DGF patients, 70 recovered from DGF and 34 incompletely recovered from DGF. Death-censored graft survival rates for control, recovered DGF, and incompletely recovered DGF groups were 95.3%, 94.7%, and 80.7%, respectively, at 5 years post-transplantation (P = 0.003). Incompletely recovered DGF was an independent risk factor for death-censored graft loss (HR = 3.410, 95%CI, 1.114-10.437). DGF was associated with increased risk for patient death regardless of DGF recovery status. Mean GFRs at 5 years were 65.5 ± 20.8, 62.2 ± 27.0, and 45.8 ± 15.4 mL/min/1.73 m2 for control, recovered, and incompletely recovered DGF groups, respectively (P < 0.001). Control group and recovered DGF patients had similar renal outcomes. However, DGF was associated with increased risk for patient death regardless of DGF recovery status.